Environmental Incidents, Pemberitaan Media dan Praktik Pengungkapan Sustainability Report - Ayu Ambang Lestari -; Fitri Nabila; Arie Cahyani (PRODUCTIVITY: Journal of Integrated Business, Management, and Accounting Research, 2025)
Around 70% of environmental damage in Indonesia is caused by mining activities. Companies should make contributions as a form of social responsibility to various problems caused by company activities and present them in sustainability reports. This study aims to examine environmental incidents, media coverage and sustainability report disclosure practices. This study uses content analysis techniques, the data used are secondary data from the sustainability reports of state-owned mining sector companies in 2020-2022 and news in the mass media about environmental incidents. The results of the study show that the average disclosure of social responsibility of PT Aneka Tambang (ANTAM) in 2020-2022 was 56%, 58% and 92%, the average disclosure of PT Timah's social responsibility in 2020-2022 was 49%, 53% and 95% and the average disclosure of social responsibility of PT Bukit Asam Tbk in 2020-2022 was 78%, 58% and 88%. Meanwhile, media coverage focuses more on conveying negative news resulting from the company's operational activities compared to news that contains the company's efforts to overcome environmental damage. This also has an impact on increasing disclosure in sustainability reports. This research contributes to improving the quality and transparency of sustainability reports, especially in terms of disclosing environmental incidents